Groovy and Grails Recipes - Jawad, Bashar (Springer, 2017)
Groovy and Grails Recipes is the busy developer's guide to developing applications in Groovy and Grails. Rather than boring you with theoretical knowledge of “yet another language/framework,” this book delves straight into solving real–life problems in Groovy and Grails using easy–to–understand, well–explained code snippets. Through learning by example, you will be able to pick up on Groovy and Grails quickly and use the book as an essential reference when developing applications.